Hadith #7441 - Sahih Muslim - Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد (Sahih Muslim)
‘Go to Jarīr bin Hāzim and say to him, ‘It is not allowed for you to transmit from al-Hasan bin Umārah for indeed he lies’.’ Abū Dāwud said, I said to Shu’bah: ‘And how do you know that?’ So said: ‘It is transmitted on authority of al-Hasan al-Basrī’.’ Al-Hasan bin Umārah said: ‘Al-Hakam narrated to us, on authority of Yahyā bin al-Jazzār, on authority of Alī.
Grade: Sahih

Hadith #7443 - Sahih Muslim - Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد (Sahih Muslim)
‘You transmit a great deal on authority of Abbād bin Mansūr – so how is it that you did not hear the Ḥadīth of ‘the lady perfume seller’ from him which an-Naḍr bin Shumayl transmitted to us?’ so we abandoned him ’.
Grade: Sahih